New insight into effective biosorption of lead from aqueous solution using Ralstonia solanacearum: Characterization and mechanism studies. (10th February 2018) - Pugazhendhi, Arivalagan; Boovaragamoorthy, Gowri Manogari; Ranganathan, Kuppusamy; Naushad, Mu; Kaliannan, Thamaraiselvi
Abstract: Among the heavy metals, lead is one of the toxic metals which is being released into the environment through various anthropogenic sources and they are of serious threat to the ecosystem. Hence in this study, we have made efforts to utilize bacteria for the removal of lead. The lead resistant bacterial strain namely, Ralstonia solanacearum KTSMBNL 13 was isolated from heavy metal polluted electroplating industrial soil. Factors affecting the removal of lead namely, initial lead ion concentration, solution pH, temperature and contact time were investigated. Results showed that maximum removal of lead was attained (90%) at an initial pH value of 6.0, temperature of 35 °C and contact time of 26 h with an initial metal concentration of 100 mg L −1 . In order to identify the functional groups involved in the uptake of lead ions, FTIR, SEM–EDX, TEM and XRD analysis were carried out. Also the antibiotic sensitivity test for Ralstonia solanacearum KTSMBNL 13 was carried out and it was found that the isolate was sensitive to gentamicin, streptomycin and tobaramycin among the tested 12 antibiotics. From the outcome of the results, it has been demonstrated that Ralstonia solanacearum KTSMBNL 13 is a novel bacteria which can be used as an alternative and promising candidate and can be applied to remove lead from various metal contaminated sites. Graphical abstract: Image